Ethical standards for technological and business education sustainability - Dhaen, Esra Al; Gallear, David; Weerakkody, Vishanth; Chen, Weifeng (Technological innovation and sustainability for business competitive advantage, 2025)
Business Education is considered a driver of change through integrating multidisciplinary skills and knowledge as part of teaching and learning. However, the nature of technological advancements used in teaching, learning and assessments varies in different contexts. Ethical Standards for Technological and Business Education Sustainability explores different uses of technology, including revising pedagogical standards, innovative teaching methods, inclusion of technological advancement as part of lifelong learning, and use of technology as part of formative learning and assessments. The chapters provide an insight into new policies and procedures to be developed to ensure academic integrity, quality of education and avoidance of academic misconduct specifically for technological and business education. The book will support policy makers, leaders of higher education, academics, and regulators to set a new dimension of policies and standards to support development of clear guidelines to maintain ethical use of technology in business education. The TISBCA series emphasises the scientific exploration of business challenges faced by organizations, while offering practical solutions. By contributing to the development and enhancement of business theories and practices, and by promoting scientific research in technological innovation and sustainability, the volumes facilitate meaningful dialogues among academics, practitioners, and individuals. The research presented connects traditional accounting, auditing and internal control practices with the cutting-edge technological advancements that are revolutionising the way business transactions are conducted.